AN ECONOMIC ANALYSIS OF GOVERNMENT INTERVENTION MEASURES IN THE COCONUT INDUSTRY OF SRI LANKA - H W S de Silva (International Coconut Community, 1985)
The apparent objectives of the govemment intervention measures in the coconut industry are identified and ranked. The inadequacy of data prevents estimation of basic coefficients required for the analysis. The partial equilibrium‑analysis based on “a prior' expectations shows that the opportunities available to improve the tenns of trade in desiccated coconut and edible copra exports justify government intervention in these two products in the foriu of export duties. There may also be some justification for expanding extension services and public investment on coconut researeh, which enables to realise the production objective of government. The implications of the study crucially depend on the assumptions and the partial equilibrium technique used.